Vietnamese financial institutions in the aftermath of Covid-19 - Le, Van; Tran, Anh Tung; Tran, Thi Trang (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
This article points to look for the proper methodologies for financial institutions in Vietnam within the consequence of Covid-19 widespread. Inside an interesting setting, the widespread has coincidently made formative chances for money related issues. Beneath this circumstance along the quickening handle of computerized change, this article appears that monetary educate should concentrate on research and advancement for human capital and innovation within the post-pandemic period. Such techniques are anticipated to encourage successful competition in terms of item contrasts and ideal costs as well as maintainable improvement based on budgetary, clientele, handling, and preparing components.